2022
DOI: 10.1007/s40194-021-01224-x
|View full text |Cite
|
Sign up to set email alerts
|

Overview on the digitized production of welded steel structures

Abstract: This paper presents a concept and practical topics involved in digitized production. The term “production” denotes the design, fabrication, and service life of a product, which in this case elaborates on welded steel structures. This includes the required information for guiding all the process stages of the chosen material back to its re-melting, following the material flow in a fully digitized form. This concept enables an increase in production quality at a higher level while minimizing the risk of human er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been observed that conventional, non-stiffened steel plate walls underperform, displaying low stiffness and significant deformation. Furthermore, the transportation and subsequent assembly of box-plate modular steel structures necessitate extensive on-site welding, a process linked to structural impairments such as cracks and fractures, as documented in references [1][2][3]. Thus, the exploration of stiffened steel plate walls with enhanced hysteresis characteristics, increased stiffness, and greater strength, particularly considering the effects of welding on the shear resistance of walls in box-plate modular structures, has become a primary research interest in both engineering and academic domains…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that conventional, non-stiffened steel plate walls underperform, displaying low stiffness and significant deformation. Furthermore, the transportation and subsequent assembly of box-plate modular steel structures necessitate extensive on-site welding, a process linked to structural impairments such as cracks and fractures, as documented in references [1][2][3]. Thus, the exploration of stiffened steel plate walls with enhanced hysteresis characteristics, increased stiffness, and greater strength, particularly considering the effects of welding on the shear resistance of walls in box-plate modular structures, has become a primary research interest in both engineering and academic domains…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they provide geometrical shape change which causes increasing of the stresses in the transition zone from the weld to the base metal. This phenomenon known as stress concentration is one of the main factors which determine the fatigue life of welded joints [4]. It is well known that stress concentration should be taken into account not only under vibration, but also under static loading, when brittle fracture is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The post-treatment of welding joint is close correlation with the structural integrity (Koncsik, 2019; Koncsik, 2021) of both the welding joint and the welded structural element or structure. Furthermore, the post-treatment techniques can be inserted in the digitized production philosophy (Skriko et al, 2022), under digitized fabrication.…”
Section: Introductionmentioning
confidence: 99%